STUDY OF THE OPTICAL REFRACTIVE INDEX NANOCOMPOSITE MATERIALS - Shylenko, D.R.; Marchenko, A.V.; Pysarenko, O.A.; Dubyna, V.O.; Belyaev, E.V. (World of Medicine and Biology, 2012)
In this article presents there results of the study of absolute refractive optical nanocomposite materials with light stripes Bekke. The achieved results showing the influence of fillers on refractive index materials. Multi-layer art restoration algorithms are formed with the goal of reliable transmission of optical fluorescence of a tooth.
Keywords: fluorescence; optical refraction; nanocomposite; filler